Comparison of serum cardiac specific biomarker release after non-cardiac thoracic surgery - Muley, Thomas; Kurz, Markus; Männle, Clemens; Alekozai, Adjmal; Winteroll, Susanne; Dienemann, Hendrik; Schmidt, Werner; Pfannschmidt, Joachim (Clinical laboratory, 2011)
BACKGROUND: The detection of postoperative myocardial infarction can be difficult in patients after lung surgery. The aim of this study was to verify the clinical significance of elevated Troponin I (cTnI), N-terminal pro-natriuretic peptide (NT-pro-BNP), lactate dehydrogenase (LDH), creatine kinase (CK), and CK-MB in the perioperative course. - METHODS: Between 2007 and 2010, 64 patients (36 men, 28 women) were includeded in this prospective study and underwent thoracotomy and wedge lung resection (n = 20, group I), lobectomy/bilobectomy (n = 24, group II), and pneumonectomy (n = 20, group III). Peri-operative measurements were done for the serum markers: cTnI, NT-pro-BNP, LDH, CK, and CK-MB preoperatively and at 4 hours, 8 hours, and 24 hours postoperatively. Patients were followed over a 90-day period to evaluate postoperative cardiac mortality. - RESULTS: No basal troponin I elevation (or CK-MB) was found prior to surgery. Elevation in concentrations of troponin I (> 0.32 ng/mL) occurring after the procedure were seen in 9 patients. However, there was neither association with 90-day survival, postoperative ECG changes, nor with elevated levels of the other cardiac serum markers. cTnI correlated significantly with intrapericardial procedures in 7 out of 20 patients (Spearman's rank correlation coefficient: 0.406; p < 0.0001). Additionally, of the 20 patients within the pneumonectomy group, 8 patients had postoperative elevated serum cTnI. The grouping of patients into groups I through III was significantly associated with cTnI elevation (Spearman's rank correlation coefficient: 0.455; p < 0.0001). - CONCLUSIONS: Despite the excellent sensitivity of troponin I for detection of acute myocardial infarction the fact remains that troponin I elevations were common after intrapericardial procedures and pneumonectomies. Thus, to differentiate between cardiac ischemia provoked chest pain and wound pain related to thoracotomy remains most difficult. Patients with only marginally elevated cTnI concentrations after intrapericardial resections or pneumonectomy should remain in the intensive care unit and should be followed-up carefully by cardiologists.
Gesehen am 14.09.2022